Manejo integral clínico del bruxismo - Castillo García, Juan Manuel; Jalmes Montes, Ana Fernanda (Revista Estomatología, 1997)
Bruxism is the unfunctional movement of the lower teeth against the upper teeth, generally it occurs unconsciously. It can be clasified as diuranl bruxims or centric bruxims and nocturnal or excentric bruxims. Bruxims has a multifatorial etiology which includes local oclusal factors and others, for a good treatment these factors must be eliminiated. The diagnostic is based on clinical sintoms and signs, a complete clinical history, and a occlusal analisis. Bruxims produces several changes in the stomatogmatic system these are noticed on teeth, muscle, bones and temporo-mandibular joints.